(111)-oriented Sn-doped BaTiO3 epitaxial thin films for ultrahigh energy density capacitors. Issue 19 (1st October 2021) - Kim, Tae Yeon; Choi, Je Oh; Anoop, Gopinathan; Kim, Jaegyu; Park, Seong Min; Samanta, Shibnath; Choi, Wooseon; Kim, Young-Min; Hong, Seungbum; Jo, Ji Young
Abstract: Despite the significant advancements of dielectric materials, the energy density values of dielectric capacitors are extremely low compared to those of other energy storage systems, e.g., batteries and fuel cells. The deposition of solid solution of ferroelectric and paraelectric multicomponent thin films are the most widely used approach to enhance the energy density of dielectric capacitors; however, it is extremely difficult to determine the optimized composition ratio of two or three components. In this study, we develop ultrahigh energy density single-component Sn-doped BaTiO3 (BTS) epitaxial thin film capacitors. An ultrahigh energy density of 92.5 J/cm 3 and energy efficiencies above 78% were successfully achieved in (111)-oriented BTS epitaxial thin film capacitors. These excellent results were attributed to the formation of multi-nanodomains accompanied by delayed polarization saturation, low remnant polarization, high breakdown strength, and high cycling stability. Engineering multi-nanodomains through chemical doping and epitaxial orientation is a facile approach to develop energy-efficient ultrahigh energy density capacitors. This approach can be extended for the design of other single-component-based energy-efficient dielectric capacitors with ultrahigh energy density. Graphical abstract: Image 1